Weak Regulations, Harmed Consumers: An Evaluation of Digital Consumer Protection Mechanisms - Nugraheni, Chyntia Regita; Khaerudin, Ariy; Dewi, Nourma (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2025)
The rapid growth of e-commerce in Indonesia has led to the rise of self-regulatory practices, particularly in the form of standard clauses unilaterally imposed by digital platforms. This development presents potential risks to the protection of consumer rights as stipulated in the Consumer Protection Law. This study aims to examine the presence of standard clauses within self-regulation, identify potential violations of consumer rights, and assess the effectiveness of existing legal protection mechanisms. A normative juridical method is employed, utilizing a statutory approach and case studies involving major e-commerce platforms in Indonesia. The findings reveal that many standard clauses fail to uphold the principles of fairness, transparency, and consumer safety. Moreover, the internal dispute resolution mechanisms provided by these platforms are often ineffective and tend to favor business actors. In conclusion, regulatory intervention and enhanced oversight of self-regulatory practices are necessary to ensure the optimal protection of consumer rights.